2014
DOI: 10.1007/s00259-014-2833-4
|View full text |Cite|
|
Sign up to set email alerts
|

Role of [18F]FDG PET in prediction of KRAS and EGFR mutation status in patients with advanced non-small-cell lung cancer

Abstract: NSCLC patients with tumours harbouring KRAS mutations showed significantly higher [(18)F]FDG uptake than WT patients, as assessed in terms of SUVpeak, SUVmax and SUVmean. A multivariate model based on age, gender, AJCC stage and SUVmean might be used as a predictive marker of KRAS mutation status in patients with stage III or IV NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
4
58
3
Order By: Relevance
“…Moreover, we also found that the feature distributions between KRAS1 and KRASwere not significantly different for any of the PET features. However, these differences may also be attributed to the different cohort size because we investigated the association between PET imaging features and mutation status in 348 tumors, whereas the study by Caicedo et al (19) investigated 102 tumors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, we also found that the feature distributions between KRAS1 and KRASwere not significantly different for any of the PET features. However, these differences may also be attributed to the different cohort size because we investigated the association between PET imaging features and mutation status in 348 tumors, whereas the study by Caicedo et al (19) investigated 102 tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Caicedo et al (19) investigated whether SUV measures, including maximum, peak, and average SUV, could predict EGFR and KRAS mutation status in 102 patients with NSCLC. Unlike our results, they found that KRAS1 tumors had significantly higher values in SUV measures than both EGFR mutants and KRAS-EGFR WTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative noninvasive strategies, such as PET/CT, for predicting the mutation profile would therefore be of great value. Several studies have demonstrated that PET/CT has the potential to predict the phenotype of a tumor (8)(9)(10)(11), such as the KRAS status in colorectal cancer (9,10) and the lactate dehydrogenase A expression level in lung adenocarcinoma (12), the latter being useful for treatment strategies involving lactate dehydrogenase A inhibitor. 18 F-FDG PET/CT has been widely used for diagnosis, monitoring of treatment response, surveillance, and prognostication in a variety of cancers (13)(14)(15).…”
mentioning
confidence: 99%
“…The study by Kawada et al (8) was the first clinical study showing the causal relationship between KRAS mutations and 18 F-FDG accumulation using 18 F-FDG PET/CT scans in a variety of cancers. There is also emerging evidence from other groups that 18 F-FDG accumulation reflects KRAS mutational status of CRC and non-small cell lung cancer (11)(12)(13). However, the clinical utility of these findings has been limited because endoscopic biopsy for KRAS mutational testing is safe and feasible only in primary CRC.…”
mentioning
confidence: 99%